The circRNA-miRNA/RBP regulatory network in myocardial infarction - Zhang, Lei; Zhang, Yuan; Yu, Fei; Li, Xin; Gao, Huijuan; Li, Peifeng (Frontiers in Pharmacology, 2022)
Myocardial infarction (MI) is a serious heart disease that causes high mortality rate worldwide. Noncoding RNAs are widely involved in the pathogenesis of MI. Circular RNAs (circRNAs) are recently validated to be crucial modulators of MI. CircRNAs are circularized RNAs with covalently closed loops, which make them stable under various conditions. CircRNAs can function by different mechanisms, such as serving as sponges of microRNAs (miRNAs) and RNA-binding proteins (RBPs), regulating mRNA transcription, and encoding peptides. Among these mechanisms, sponging miRNAs/RBPs is the main pathway. In this paper, we systematically review the current knowledge on the properties and action modes of circRNAs, elaborate on the roles of the circRNA-miRNA/RBP network in MI, and explore the value of circRNAs in MI diagnosis and clinical therapies. CircRNAs are widely involved in MI. CircRNAs have many advantages, such as stability, specificity, and wide distribution, which imply that circRNAs have a great potential to act as biomarkers for MI diagnosis and prognosis.